XBREACH OF CONSIGNMENT AGREEMENT BETWEEN ADEE CAKE MANUFACTURER AND SMALL TRADERS (RESEARCH STUDY IN MEUREUDU DISTRICT, PIDIE JAYA REGENCY) - Aisyah; Teuku Yudi Afrizal; Tri Widya Kurniasari (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aim For know implementation agreement consignment between manufacturers and traders small cake Adee in the District Meureudu , Pidie Jaya Regency , as well analyze factor reason occurrence default and efforts settlement dispute in agreement The problems studied​​ related with practice agreement consignment in general done in a way oral based on principle trust , so that in implementation cause problem law in the form of delay payment results sales , implementation obligations that are not perfect , or No fulfilled achievements by traders to manufacturer . Research This use method qualitative with approach juridical empirical and nature study descriptive analytical . Research data obtained through interviews , observations , and documentation to manufacturer as well as trader small cake Adee in the District Meureudu , Pidie Jaya Regency , which then analyzed in a way qualitative . Research results show that implementation agreement consignment Still based on trust without agreement written . Causal factors occurrence default covering use results sale For interest personal , condition business traders who experience difficulties , as well as weakness supervision in implementation agreement . Form default that occurred in the form of delay payment , implementation achievements that are not appropriate , and not carry out performance The same once . Completion dispute done non - litigation through deliberation and negotiation For maintain connection Work The same between the parties . It is recommended that producers and traders small make agreement consignment in a way written to provide certainty law for the parties .